Insect Molecular characterization ElaeidobiuskamerunicusFaust. (Coleoptera; Curculionidae) Origin North Sumatra Method Using Amplified Fragment Length Polymorphism (AFLP) - muhammad riza fahlevi; Darma Bakti; Suzanna Fitriany Sitepu (Universitas Sumatera Utara, 2017)
Elaeidobius kamerunicus introduced to Indonesia in Palm Research Center, Marihat. It is one pollinator to pollinate palm. Genetic changes in these insects cause a decline in palm oil production. The purpose of this study to determine the genetic diversity of it based molecular analysis techniques AFLP using three primers. Primers used are HEX (EcoR1 ACA - Mse1 CTT), FAM (EcoR1 AGG - Mse1 CAG) and FAM (EcoR1 AGG - Mse1 CTT). Analysis of genetic diversity using the MEGA program version 6. Phylogenetic tree using 'Neighbor-Joining Tree'. AFLP amplification product to 42 samples of genomic it and 3 Sitophilus oryzae genomic sample as a control showed a high diversity. The analysis showed that itgenetically grouped separately with S. oryzae. It contained in districts in North Sumatra has two large groups : group A1 and A2. Group A1 consisting of Ajamu, Bah Birong Ulu, Binanga, Bukit Sentang, Marihat, Padang Madarsah and PT. TPS Sibolga while the Group A2 consists of two regions, namely Marihat and Bah Birong Ulu while S. oryzae contained in Medan form their own group.